ASSESSMENT OF WATER AND ENVIRONMENTAL SANITATION SERVICES OF PRIMARY EDUCATION (KHALWA) AT EAST NILE LOCALITY, SUDAN, 2017 - Mohamed, Hadeel; Ali, Fatima Fadul; Elamin, Mohamed Osman; Faraj, Elmubasher Abd (International Journal of Research -GRANTHAALAYAH, 2018)
The descriptive study was conducted in East Nile locality in the period of September to December 2017 to assess the water and environmental sanitation services of primary education instituations (Khalwa). Unsafe water, inadequate sanitation, and insufficient hygiene practices account for an estimated 9.1 percent of the global burden of disease and 6.3 percent of all deaths. The study aimed to assess the healthy environment, the availability of water supply and water services in khalwas, the ways of collection and disposal of solid waste and health awareness among students towards personal hygiene. The students (384students) selected randomly from (5135students) and the data was collected by questionnaire and checklist from 4khalwas. The study results revealed that (96.4%) of students their education level is just khalwa, (32.8%) of students don’t know the important of personal hygiene, (50%) of khalwas the source of water is wells, (50%) of khalwas don’t have containers for solid waste and it’s burning solid waste and (75%) of khalwas have just two meals per day. The study was recommended that to increase the awareness of students towards personal hygiene, provision of containers and cars for solid waste in each khalwas, providing network for drinking water and for wastewater and increase the number of rooms according to the number of students.